Der Dreigroschenoper - Pabst, Georg Wilhelm (Germany, 1931)
In the last few years before Nazi power overtook the German film industry, Kurt Weill's operetta reached the screen in this effective and well-cast version. Notable for including Lotte Lenya (Weill's wife) as Jenny, it is funny, memorable, and imaginatively filmed. An adaptation of Bertolt Brecht's famous play, the plot revolves around the underworld of crooks, moneylenders, and cut-throats. In London at the turn of the century, the bandit Mack the Knife marries Polly without the knowledge of her father, Peachum, the 'king of the beggars'. Chief of note in the varied cast are Rudolf Forster as Mackie, Carola Neher as Polly, Fritz Rasp as Peachum, and Ernst Busch as the Street Singer.
Duration: 01:47:00
Keywords: Germany